Effective Protection by Transportation Costs and Tariffs: A Comparison of Magnitudes - Finger, J. M.; Yeats, A. J. (Quarterly Journal of Economics, 1976)
I. Introduction, 169. — II. The data and methodology, 170. — III. Comparisons of levels, 173. — IV. Recent changes in transport costs, 174. — V. Conclusions, 175.